2019
DOI: 10.1039/c9ra04782d
|View full text |Cite
|
Sign up to set email alerts
|

Enantiopure polythiophene nanoparticles. Chirality dependence of cellular uptake, intracellular distribution and antimicrobial activity

Abstract: The use of intrinsic chiral molecules opens the door to bio-imaging specific tools and to the development of target-therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…E. coli DH5-α have been developed with several mutations to obtain high-efficiency transformation [ 31 ]. Many pores and appendices present in the cellular envelope of DH5-α bacteria could confer the distinctive antibacterial response to the extracts from the other strains [ 32 , 33 ].…”
Section: Results and Decisionmentioning
confidence: 99%
“…E. coli DH5-α have been developed with several mutations to obtain high-efficiency transformation [ 31 ]. Many pores and appendices present in the cellular envelope of DH5-α bacteria could confer the distinctive antibacterial response to the extracts from the other strains [ 32 , 33 ].…”
Section: Results and Decisionmentioning
confidence: 99%
“…The residual organic solvent can be removed by evaporation under reduced pressure or by dialyzing the colloidal suspension 35 . Chart 1 reports the chemical structures of different PTs that have been reported to form NPs following this methodology 37–49 …”
Section: Synthesis Of Semiconducting Pt‐npsmentioning
confidence: 99%
“…It has also been reported that it is possible to prepare chiral PT‐NPs by functionalizing the side chains of polymers with enantiopure R or S chiral moieties 45 . Chiral nanoobjects may interact differently with chiral biomolecules and affect physiological events 101 .…”
Section: Biological Applications Of Pt‐npsmentioning
confidence: 99%
“…Because the direct self-assembly approach does not alter the chemical structures of CPs, it preserves the best properties of CPs as originally designed. Water-dispersible P3HT NPs have been extensively explored through two different methods, namely nanoprecipitation ( Fraleoni-Morgera et al., 2004 ; Palamà et al., 2019 ; Shimizu et al., 2008 ; Zangoli et al., 2017 ; Zucchetti et al., 2017 ) and microemulsion ( Nagarjuna et al., 2012 ). In nanoprecipitation, P3HT dissolved in a good solvent like tetrahydrofuran (THF) is slowly added to water as a non-solvent for P3HT.…”
Section: Introductionmentioning
confidence: 99%